Overview of complexity: main currents, definitions and constructs - Lukosevicius, Alessandro Prudêncio (2017)
The Theory of Complexity is applied to many fields of human knowledge, and its implications are increasing, both in the market and in academia. However, usually the theory is approached by fragments in literature reviews, which does not have it as its main focus. In this way, it is difficult to understand their uniqueness, their continuity and their consistency. Thus, the objective of this work is to provide a panorama about Complexity Theory, presenting its main elements and fomenting the discussion about its potentialities of use. The research approach is qualitative, exploratory and bibliographical, focused on three of the main scientific bases: Web of Knowledge, Scopus and SciELO Brazil. It is noted that the popularity of Complexity Theory between academics and practitioners is increasing and has the potential to generate benefits not yet explored in several areas.